Long Noncoding RNA 00472: A Novel Biomarker in Human Diseases - Ren, Dan-yang; Yuan, Xin-rong; Tu, Cai-xia; Shen, Jian-ling; Li, Yun-wei; Yan, Ai-hua; Ru, Yi; Han, Hui-yun; Yang, Yan-ming; Liu, Yan; Li, Hui-ying (Frontiers in Pharmacology, 2021)
Long non-coding RNAs (lncRNAs) play important roles in human diseases. They control gene expression levels and influence various biological processes through multiple mechanisms. Functional abnormalities in lncRNAs are strongly associated with occurrence and development of various diseases. LINC00472, which is located on chromosome 6q13, is involved in several human diseases, particularly cancers of the breast, lung, liver, osteosarcoma, bladder, colorectal, ovarian, pancreatic and stomach. Importantly, LINC00472 can be used as a biomarker for breast cancer cell sensitivity to chemotherapeutic regimens, including doxorubicin. LINC00472 is regulated by microRNAs and several signaling pathways. However, the significance of LINC00472 in human diseases has not been clearly established. In this review, we elucidate on the significance of LINC00472 in various human diseases, indicating that LINC00472 may be a diagnostic, prognostic as well as treatment target for these diseases.